Alcohol Abuse Is Associated With Alterations in Corneal Endothelial Cell Morphology. Issue 4 (25th April 2023) - Karmakar, Ranit; Nooshabadi, Saeid; Lohmeier, John; Terrin, Staci; Eghrari, Allen O.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: Alcohol consumption is highly prevalent throughout the world. We sought to detect, in a large sample of cornea donors, whether alcohol abuse is associated with changes in corneal endothelial morphology after accounting for other comorbidities including tobacco use. Methods: At a single eye bank, 10, 322 eyes from a total of 5624 unique donors underwent imaging with a Konan CellChek D specular microscope. Demographic information and medical history were associated with each tissue. Images were analyzed using a standardized protocol for assessment of endothelial cell density, hexagonality, and variation. In this retrospective analysis, a multivariable regression was conducted to assess for an association between alcohol abuse and corneal endothelial metrics. Measurements were averaged across eyes for each donor. Bonferroni corrections were applied to account for multiple comparisons. Results: Among 5624 donors, the mean (standard deviation) endothelial cell density was 2785 (383.0) cells/mm 2 . Indicators of alcohol abuse were present in 1382 donors (24.5%). In a multivariable regression model that included age, sex, tobacco use, history of cataract surgery, and diabetes mellitus, alcohol abuse was associated with a decrease of 60.9 cells/mm 2 [95% confidence interval (CI), −83.0 to −38.7 cells/mm 2, P = 7.6 × 10 −8 ], an increase in the coefficient of variation by 0.0048 (95% CI, 0.17–0.79, P = 0.002), and a decrease in percent hexagonality by 0.93% (95% CI, −1.3 to −0.6, P = 4.5 × 10 −7 ). Conclusions: Alcohol abuse is associated with significant alterations to corneal endothelial density and morphology.